THE INFLUENCE OF AUDITOR EXPERIENCE, PROFESSIONAL EXPERTISE, AUDIT TRAINING, AND PROFESSIONAL SKEPTICISM ON AUDITOR ABILITY - Andriyanto, Wahyu Ari (Advances in Social Sciences Research Journal, 2021)
Auditor ability is the skill and mastery an auditor has to carry out his jobs. An auditor is required to have special abilities. In addition to technical skills, collect evidence from various witnesses in a fair, independent manner, and follow audit regulations or standards. This research is a quantitative study which aims to determine the effect of Auditor Experience, Professional Skills, Audit Training, Professional Skepticism on Auditor Ability. The population in this study were auditors who worked at the Public Accounting Firm in DKI Jakarta by using a purposive sampling technique with the criteria of being auditors at affiliated Public Accounting Firm in DKI Jakarta, auditors working as field auditors, and auditors who had attended audit training. Technical analysis of the data used is Multiple Linear Regression Analysis with the SPSS 25 program and a significance level of 5% (0.05). The results obtained were (1) Auditor's experience had a significant effect on the auditor's ability, (2) Professional expertise had a significant effect on the Auditor's ability, (3) Audit training had no effect on the Auditor's ability, and (4) Professional skepticism had no effect on the Auditor's ability.